Physiologically Based Pharmacokinetic Modeling Approach to Predict Drug‐Drug Interactions With Ethionamide Involving Impact of Genetic Polymorphism on FMO3. (28th January 2019) - Nguyen, Phuong Thi Thu; Parvez, Md Masud; Kim, Min Jung; Yoo, Sung Eun; Ahn, Sangzin; Ghim, Jong‐Lyul; Shin, Jae‐Gook
Abstract: The widely used second‐line antituberculosis drug ethionamide shows wide interindividual variability in its disposition; however, the relevant factors affecting this phenomenon have not been characterized. We previously reported the major contribution of flavin‐containing monooxygenase 3 (FMO3) in the reductive elimination pathway of ethionamide. In this study, ethionamide metabolism was potentially inhibited by methimazole in vitro. The drug‐drug interaction leading to methimazole affecting the disposition of ethionamide mediated by FMO3 was then quantitated using a bottom‐up approach with a physiologically based pharmacokinetic framework. The maximum concentration (Cmax ) and area under the curve (AUC) of ethionamide were estimated to increase by 13% and 16%, respectively, when coadministered with methimazole. Subsequently, we explored the effect of FMO3 genetic polymorphism on metabolic capacity, by constructing 2 common functional variants, Lys 158 ‐FMO3 and Gly 308 ‐FMO3. Compared to the wild type, recombinant Lys 158 ‐FMO3 and Gly 308 ‐FMO3 variants significantly decreased the intrinsic clearance of ethionamide by 2% and 24%, respectively. Two prevalent functional variants of FMO3 were predicted to affect ethionamide disposition, with mean ratios of Cmax and AUC of up to 1.5 and 1.7, respectively, in comparison with the wild type. In comparing single ethionamide administration with the wild type, simulations of the combined effects of comedications and FMO3 genetic polymorphism estimated that the Cmax and AUC ratios of ethionamide increased up to 1.7 and 2.0, respectively. These findings suggested that FMO3‐mediated drug‐drug interaction and genetic polymorphism could be important determinants of interindividual heterogeneity in ethionamide disposition that need to be considered comprehensively to optimize the personalized dosing of ethionamide.